An Efficient Downlink Data Mapping Algorithm for IEEE802.16e OFDMA Systems - Xin Jin; Jihua Zhou; Jinlong Hu; Jinglin Shi; Yi Sun; Dutkiewicz, E. (Globecom (2003), 2008)
In the IEEE 802.16e OFDMA systems, the data mapping algorithm maps the data to the appropriate rectangular regions in the two-dimensional matrix of time and frequency domain. Each region is described by an Information Element (IE) which is used for signaling and occupies a slot. The IEs as well as vacant slots in the allocated rectangular region result in a substantial amount of overhead. In order to minimize the overhead so as to increase system throughput, the paper proposes a "Mapping with Appropriate Truncation and Sort" (MATS) algorithm. Extensive simulations are conducted in terms of mapping efficiency, mapping cost and system throughput to evaluate the performance of MATS. The results show that compared with Raster, MATS can increase the mapping efficiency by up to 2.4% and reduce the mapping cost by up to 80% and 37% for constant bit rate traffic and variable bit rate traffic, respectively. Moreover, system throughput is increased by more than 3% in the 10 MHz bandwidth network. Consequently, MATS can substantially reduce the overhead and achieve high system throughput.